Lattice vibrational behavior and thermodynamic properties of uranium disilicide USi2. (December 2016) - Yang, Jin-Wen; An, Li
Abstract: Detailed first-principles calculations under the projector augmented wave (PAW) framework are reported so as to determine the structural, elastic, crystal lattice-dynamical and thermodynamic properties of the binary α-USi2 alloy (Space Group: I41 /amd- D 4 h 19 ; Pearson: tI12) with ThSi2 -type. The calculated lattice constants a and c, and inner coordinate z, equilibrium volume V 0, bulk modulus B 0 and its pressure derivative B ′ for USi2 are compared with the available experimental and other theoretical works, and the agreements between them are quite well. In particular, for the first time, the phonon band dispersion relations and the phonon densities of states are investigated by employing the linear-response method of the density functional perturbation theory (DFPT) under non-spin polarized and spin polarized frames. The characteristics of the phonon dynamics at the center Γ point of Brillouin zone have also been assigned systematically. The present calculated results reveal that USi2 alloy with ThSi2 -type is dynamically stable at ambient conditions, and the spin polarization plays a certain role to its dynamical behavior to some extent. To gain comprehensive insight for the lattice vibration behavior of USi2, the thermodynamic properties have been calculated based on the calculated phonon densities of state (PDOS) further, however, it is found that the spin polarized effect is negligible on its thermodynamic properties. The investigations of USi2 alloy in this paper could provide essential reference data for future explorations on actinide disilicides. Highlights: The phonon properties of USi2 are investigated using DFPT method. USi2 alloy with ThSi2 -type is dynamically stable at ambient conditions. The characteristics of the phonon dynamics at Γ point of Brillouin zone are assigned. The thermodynamic properties of USi2 are obtained based on the calculated phonon densities of state.